Adhesive sheet
By laminating a adhesive layer of a monovinyl-substituted block copolymer of aromatic compound and conjugated diene compound and a tackifying resin at different softening points on the fiber sheet, the adhesive sheet between the smooth surface and the rough surface is solved. The joint problem has achieved high peel strength and good peelability, and is suitable for a variety of industrial applications.
Patent Information
- Application Number
- CN202080017880.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Priority Date
- 2019-03-06
- Filing Date
- 2020-02-13
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2040-02-13
AI Technical Summary
The existing adhesive sheets are difficult to firmly bond between the smooth surface and the rough surface and peel well from the smooth surface, especially in applications on uneven surfaces, which tend to cause residual and flexible deformation of the adhesive sheets.
Adhesive sheets containing fiber sheets and laminated adhesive layers, wherein the adhesive layer is composed of a block copolymer of monovinyl-substituted aromatic compound and a conjugated diene compound, and combined with a tackifying resin with a softening point less than 120°C With a tackifying resin with a softening point of 120°C or above, the adhesive layer thickness is between 100 μm and 190 μm, and a double-sided adhesive sheet is formed to meet the bonding needs of different surfaces.
It achieves firm adhesiveness to both smooth and rough surfaces, and avoids the residue of adhesive sheets during peeling, improves the peel strength and applicability of adhesive sheets, and is suitable for fixing applications of porous sheets and buckles.
Smart Images

Figure CN113518709B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to an adhesive sheet.
[0002] This application claims priority based on Japanese Patent Application No. 2019-041005 filed on March 6, 2019, the entire contents of which are incorporated herein by reference. Background Art
[0003] Generally, adhesives (also called pressure-sensitive adhesives; the same below) are in a soft solid (viscoelastic) state within a temperature range near room temperature, and have the property of being simply adhered to an adherend by pressure. Utilizing such properties, adhesives are widely used in various industrial fields ranging from home appliances to automobiles and office automation (OA) equipment as a joining means with good workability and high adhesive reliability. As a representative composition of an adhesive, a composition containing a polymer that exhibits rubber elasticity at room temperature as a base polymer can be cited. As a technical document related to adhesive sheets, Patent Document 1 can be cited.
[0004] Prior art literature
[0005] Patent Literature
[0006] Patent Document 1: Japanese Patent Application Publication No. 2015-78348 Summary of the invention
[0007] Problems to be solved by the invention
[0008] In the use of adhesive sheets, some require both smooth and rough surfaces to show high peel strength. As an example of such use, the use of firmly joining the smooth surface of an adherend to the rough surface of the adherend or other adherends can be cited. In recent years, from the viewpoints of effective utilization of resources and improving productivity, in addition to requiring the performance of firmly joining the smooth surface and the rough surface, an adhesive sheet that can be peeled off from the above-mentioned smooth surface as required is also required.
[0009] On the other hand, an adhesive sheet having an adhesive layer laminated on a fiber sheet such as a nonwoven fabric can be satisfactorily used in cases where the adhesive sheet is attached to an uneven surface of an adherend (e.g., a curved surface, a surface with a height difference), or where it is undesirable that the softness or deformability of the adherend be reduced by attaching the adhesive sheet. However, it is difficult to realize an adhesive sheet having such a structure that can be firmly adhered to both a smooth surface and a rough surface and has good removability from the smooth surface (e.g., the adhesive sheet is prevented from remaining on the smooth surface).
[0010] Therefore, an object of the present invention is to provide an adhesive sheet having an adhesive layer laminated on a fiber sheet, which is firmly bonded to both a smooth surface and a rough surface and has good removability from the smooth surface. Another related object is to provide an adhesive member having such an adhesive sheet bonded to a rough surface.
[0011] Means used to solve problems
[0012] The adhesive sheet provided according to the present specification comprises a fiber sheet and an adhesive layer laminated on the fiber sheet. The adhesive layer comprises a base polymer and a tackifier resin. The base polymer is a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound. The tackifier resin may contain a tackifier resin having a softening point of less than 120°C and a tackifier resin having a softening point of more than 120°C. The thickness of the adhesive layer is greater than 100 μm and less than 190 μm. According to such a structure, an adhesive sheet that is firmly bonded to both a smooth surface and a rough surface and has good removability from the smooth surface can be appropriately realized.
[0013] The adhesive sheet disclosed herein is preferably constituted in the form of a double-sided adhesive sheet, the double-sided adhesive sheet having: a first adhesive layer, the first adhesive layer being the adhesive layer laminated on the first side of the fiber sheet; and a second adhesive layer, the second adhesive layer being the adhesive layer laminated on the second side of the fiber sheet. The adhesive sheet having the above-mentioned constitution can be satisfactorily used for bonding a smooth surface (e.g., a surface with a surface roughness Sz of less than 100 μm) to a rough surface (e.g., a surface with a surface roughness Sz of 200 μm to 1000 μm).
[0014] In a preferred embodiment of the adhesive sheet disclosed herein, the adhesive sheet can be used to fix a porous sheet (brush cloth) to the core of a brush roller of a vacuum cleaner. In another preferred embodiment, the adhesive sheet disclosed herein can be used to fix an installation object to the back of a hook and loop fastener, for example.
[0015] According to the present specification, an adhesive component is also provided, which includes: a double-sided adhesive sheet, the double-sided adhesive sheet having a first adhesive layer laminated on the first side of a fiber sheet and a second adhesive layer laminated on the second side of the fiber sheet; and a sheet-like component, the sheet-like component having a rough surface with a surface roughness Sz of 200μm to 1000μm, and the second adhesive layer of the adhesive sheet is bonded to the rough surface. The first adhesive layer and the second adhesive layer can each be any one of the adhesive layers disclosed herein. The 180-degree peel strength of the adhesive component measured by pasting the first adhesive layer of the adhesive sheet on an acrylonitrile-butadiene-styrene copolymer resin (ABS) board is 25N / 20mm or more. By such an adhesive component, the sheet-like component can be firmly fixed to the adherend with good re-peelability. BRIEF DESCRIPTION OF THE DRAWINGS
[0016] [ Figure 1 ] Figure 1 This is a schematic cross-sectional view showing the structure of a pressure-sensitive adhesive sheet according to one embodiment.
[0017] [ Figure 2 ] Figure 2 It is a schematic cross-sectional view showing the structure of an adhesive member according to one embodiment. DETAILED DESCRIPTION
[0018] The preferred embodiments of the present invention are described below. It should be noted that, with respect to matters other than those specifically mentioned in this specification and necessary for the implementation of the present invention, those skilled in the art can understand based on the teachings on the implementation of the invention recorded in this specification and the technical common sense at the time of application. The present invention can be implemented based on the contents disclosed in this specification and the technical common sense in the art. In addition, in the following drawings, components and parts that play the same role are given the same symbols for description, and repeated descriptions are sometimes omitted or simplified. In addition, the embodiments described in the drawings are schematically illustrated for the purpose of clearly illustrating the present invention, and do not accurately represent the size or scale of the products actually provided.
[0019] In this specification, as mentioned above, "adhesive" refers to a material that is in a soft solid (viscoelastic) state in the temperature range near room temperature and has the property of being easily adhered to the adherend by pressure. The adhesive referred to here is defined in "CADahlquist, "Adhesion: Fundamental and Practice", McLaren & Sons, (1966) P.143", and generally speaking, it can be a material having a complex tensile elastic modulus E * (1Hz)<10 7 Dyne / cm 2 A material having the above properties at 25°C.
[0020] In this specification, the "base polymer" of the adhesive refers to the main component of the rubber polymer (polymer showing rubber elasticity in the temperature range around room temperature) contained in the adhesive, typically refers to the component accounting for more than 50% by weight of the rubber polymer.
[0021] In this specification, "block copolymers of monovinyl-substituted aromatic compounds and conjugated diene compounds" refers to polymers having at least one segment (hereinafter also referred to as "A segment") with a monovinyl-substituted aromatic compound as the main monomer (referring to more than 50% by weight of the copolymer component; the same below) and at least one segment (hereinafter also referred to as "B segment") with a conjugated diene compound as the main monomer. Usually, the glass transition temperature of the A segment is higher than the glass transition temperature of the B segment. As representative structures of the polymer, there can be listed a copolymer of a triblock structure having an A segment (hard segment) at both ends of the B segment (soft segment) (ABA structured triblock), a copolymer of a diblock structure comprising one A segment and one B segment (AB structured diblock), and the like.
[0022] In this specification, "styrene block copolymer" refers to a polymer having at least one styrene block. The above-mentioned styrene block refers to a segment with styrene as the main monomer. The segment substantially containing only styrene is a typical example of the styrene block described herein. In addition, "styrene-isoprene block copolymer" refers to a polymer having at least one styrene block and at least one isoprene block (a segment with isoprene as the main monomer). As a representative example of styrene-isoprene block copolymers, copolymers (triblocks) having a triblock structure having a styrene block (hard segment) at both ends of the isoprene block (soft segment), copolymers (diblocks) having a diblock structure containing one isoprene block and one styrene block, etc. can be cited. "Styrene-butadiene block copolymer" refers to a polymer having at least one styrene block and at least one butadiene block (a segment with butadiene as the main monomer).
[0023] In this specification, the "styrene content" of a styrene-based block copolymer refers to the weight ratio of the styrene component in the total weight of the block copolymer. The styrene content can be measured by NMR (nuclear magnetic resonance spectroscopy).
[0024] In addition, the proportion of diblocks in the styrene block copolymer (hereinafter sometimes referred to as "diblock ratio" or "diblock ratio") can be obtained by the following method. That is, the styrene block copolymer is dissolved in tetrahydrofuran (THF), and 2 sections of GS5000H and G4000H liquid chromatography columns manufactured by Tosoh Corporation are connected in series, totaling 4 sections, and THF is used as the mobile phase. High performance liquid chromatography analysis is performed under the conditions of a temperature of 40°C and a flow rate of 1 mL / min. The peak area corresponding to the diblock is determined from the obtained spectrum. Then, the diblock ratio is obtained by calculating the percentage of the peak area corresponding to the diblock relative to the total peak area.
[0025] <Structural example of adhesive sheet>
[0026] The adhesive sheet disclosed herein (which may be in the form of a tape or other long-length shape) may be, for example, Figure 1 The double-sided adhesive sheet 1 has a fiber sheet 15, a first adhesive layer 11 laminated on a first side of the fiber sheet 15, and a second adhesive layer 12 laminated on a second side of the fiber sheet 15. Figure 1 As shown, the double-sided adhesive sheet 1 before use (before being pasted to the adherend) can be a form that overlaps with a release liner 21 whose front 21A and back 21B are both release surfaces and is wound into a spiral shape. In the double-sided adhesive sheet 1 of the form, the surface (second adhesive surface 12A) of the second adhesive layer 12 is protected by the front 21A of the release liner 21, and the surface (first adhesive surface 11A) of the first adhesive layer 11 is protected by the back 21B of the release liner 21. Alternatively, it can also be a form in which the first adhesive surface 11A and the second adhesive surface 12A are protected by two independent release liners, respectively.
[0027] The PSA sheet disclosed herein may be in the form of a single-sided PSA sheet having a fiber sheet and a PSA layer laminated on a first surface thereof, and having no PSA layer on a second surface of the fiber sheet.
[0028] In the technology disclosed herein, as the release liner, conventional release paper or the like can be used without particular limitation. For example, a release liner having a release treatment layer on the surface of a substrate such as a plastic film or paper, a release liner containing a low-adhesive material such as a fluorine-containing polymer (polytetrafluoroethylene, etc.) or a polyolefin resin (polyethylene, polypropylene, etc.) can be used. The release treatment layer can be, for example, a layer formed by surface treating the substrate with a release treatment agent such as polysiloxane, long-chain alkyl, fluorine-containing, or molybdenum sulfide.
[0029] <Fiber sheet>
[0030] The adhesive sheet disclosed herein has a structure in which an adhesive layer is laminated on a fiber sheet. As the above-mentioned fiber sheet, woven or non-woven fabrics, knitted fabrics, nets, etc. obtained by spinning various fibrous substances alone or in a blend can be used. Here, non-woven fabrics refer to the concept of non-woven fabrics made using a general papermaking machine, such as Japanese paper, woodfree paper, and other papers. In addition, the concept of the above-mentioned non-woven fabrics includes felt. In the examples of the above-mentioned fibrous substances constituting the fiber sheet, in addition to the natural fibers and chemical fibers (synthetic fibers) described later, inorganic fibers such as glass fibers and carbon fibers, metal fibers, etc. are also included. It is also possible to use two or more fibrous substances of different materials in combination. The above-mentioned fiber sheet can also be understood as a supporting substrate for maintaining the adhesive layer.
[0031] There is no particular limitation on the thickness and bulk density of the fiber sheet. The thickness of the fiber sheet may be, for example, 5 μm or more, or 10 μm or more, or 100 μm or less, or 70 μm or less. The bulk density of the fiber sheet may be, for example, 0.15 g / cm 3 Above, can be 0.20g / cm 3 For example, it can be 1.00 g / cm 3 Below, can be 0.80g / cm 3 Below, can also be 0.60g / cm 3 the following.
[0032] In some embodiments of the adhesive sheet disclosed herein, a fiber sheet having a thickness of 15 μm or more and 50 μm or less can be preferably used. In addition, a fiber sheet having a bulk density of 0.25 g / cm 3 Above and 0.50g / cm 3 The PSA sheet disclosed herein can be used with a thickness of 15 μm or more and 50 μm or less and a bulk density of 0.25 g / cm 3 Above and 0.50g / cm 3 The following fiber sheet is preferably implemented. According to the fiber sheet satisfying the above-mentioned thickness and bulk density, an adhesive sheet showing higher peel strength to the adherend can be realized. As a reason for this, it is believed that the adhesive layer is strengthened by impregnating the above-mentioned fiber sheet with an adhesive, and at the same time, the strength of the above-mentioned fiber sheet is improved by the adhesive acting as a binder for the fibers constituting the above-mentioned fiber sheet, thereby preventing the adhesive sheet from peeling off in a split manner within the thickness of the fiber sheet (hereinafter also referred to as split peeling), thereby obtaining a high peel strength, but it is not particularly limited to the interpretation. The thickness of the above-mentioned fiber sheet is less than 50μm and the bulk density is 0.50g / cm 3 The adhesive can be easily impregnated into the fiber sheet, and the above-mentioned cracking and peeling can be easily suppressed. The thickness of the fiber sheet is 15 μm or more and the bulk density is 0.25 g / cm 3 As described above, it is possible to avoid the strength of the fiber sheet itself from being excessively reduced.
[0033] In some embodiments, the thickness of the fiber sheet may be, for example, less than 50 μm, less than 40 μm, less than 30 μm, less than 25 μm, or less than 20 μm. When the thickness of the fiber sheet decreases, it is easy for the adhesive to penetrate into the interior of the fiber sheet. In addition, the adhesive sheet disclosed herein can also be preferably implemented by using a fiber sheet with a thickness of 35 μm or more and 50 μm or more than 45 μm and less than 50 μm. By increasing the thickness of the fiber sheet within the above range, it is possible to balance the improvement of the strength of the fiber sheet itself and the penetration of the adhesive into the interior of the fiber sheet.
[0034] In some embodiments, the bulk density of the fiber sheet can be, for example, 0.27 g / cm 3 Above, usually preferably 0.30 g / cm 3 In a preferred embodiment, the bulk density can be greater than 0.35 g / cm 3 And less than or equal to 0.50g / cm 3 The bulk density of the fiber sheet is greater than 0.35g / cm 3 This can prevent the fiber sheet from being easily crushed in the thickness direction during the manufacture of the PSA sheet, which makes it difficult for the adhesive to penetrate therein, and can contribute to the realization of a PSA sheet in which the fiber sheet is well penetrated by the adhesive.
[0035] There is no particular limitation on the basis weight (weight per unit area) of the fiber sheet. In some embodiments, the basis weight of the fiber sheet may be, for example, about 1.0 g / m 2 ~About 100g / m 2 (Preferably about 3.0 g / m 2 ~About 50g / m 2 In some embodiments, the basis weight of the fiber sheet may be, for example, 3.8 g / m 2 Above and 25g / m 2 Below, preferably 4.5g / m 2 Above and 25g / m 2 The PSA sheet disclosed herein can be preferably implemented using a fiber sheet having a basis weight within the above range.
[0036] In a preferred embodiment of the adhesive sheet disclosed herein, as the fiber sheet, a fiber sheet having a thickness of 15 μm to 50 μm (preferably 30 μm to 50 μm, for example 45 μm to 50 μm) and a bulk density of 0.25 g / cm 3 ~0.50g / cm 3 (Preferably greater than 0.35 g / cm 3 And less than or equal to 0.50g / cm 3 , more preferably 0.40 g / cm 3~0.50g / cm 3 , for example 0.45 g / cm 3 ~0.50g / cm 3 ), basis weight is 15g / m 2 Above and 25g / m 2 Below (preferably 18g / m 2 Above and 25g / m 2 Below, for example, 21g / m 2 Above and 25g / m 2 When the adhesive layer described later is laminated on such a fiber sheet (e.g., nonwoven fabric), an adhesive sheet having high peel strength to an adherend can be appropriately realized. In the above method, the thickness of the adhesive sheet is appropriately about 4.0 to about 8.0 times the thickness of the fiber sheet, and is preferably set to about 4.5 to about 6.5 times.
[0037] In another preferred embodiment of the adhesive sheet disclosed herein, as the fiber sheet, a fiber sheet having a thickness of 15 μm to 50 μm (preferably 15 μm to 25 μm, for example 15 μm to 20 μm) and a bulk density of 0.25 g / cm 3 ~0.50g / cm 3 (Preferably greater than 0.35 g / cm 3 And less than or equal to 0.50g / cm 3 , more preferably greater than 0.35 g / cm 3 And less than or equal to 0.40g / cm 3 ), basis weight less than 10g / m 2 (typically greater than or equal to 4.5 g / m 2 And less than 10g / m 2 , preferably greater than or equal to 5.0g / m 2 And less than 10g / m 2 , for example, greater than or equal to 5.0g / m 2 And less than 8.00g / m 2 ) fiber sheet. When the adhesive layer described later is laminated on such a fiber sheet (e.g., nonwoven fabric), an adhesive sheet showing high peel strength to an adherend can be appropriately realized. In the above method, it is appropriate to set the thickness of the adhesive sheet to about 10 to about 30 times the thickness of the fiber sheet, preferably about 12 to about 25 times, and more preferably about 15 to about 20 times.
[0038] In some forms of the adhesive sheet disclosed herein, nonwoven fabrics can be preferably used as the above-mentioned fiber sheets. As nonwoven fabrics, for example, nonwoven fabrics made of pulps such as wood pulp and hemp pulp, natural fibers such as cotton, hemp (such as Manila hemp), wool, and silk can be used; nonwoven fabrics made of polyester fibers such as polyethylene terephthalate (PET) fibers, rayon, vinylon, acetate fibers, polyvinyl alcohol (PVA) fibers, polyamide fibers, polyolefin fibers, polyurethane fibers and other chemical fibers (synthetic fibers) can be used; nonwoven fabrics made of two or more fibers of different materials; etc. Among them, from the perspective of the impregnation and strength of the adhesive, nonwoven fabrics with pulps such as wood pulp and hemp pulp (for example, hemp pulp made of Manila hemp as a raw material) as the constituent fibers, nonwoven fabrics made of wool, nonwoven fabrics made of PET fibers, etc. are preferred.
[0039] In addition to the fibrous material described above, the fiber sheet (e.g., nonwoven fabric) may also contain resin components such as starch (e.g., cationized starch), polyacrylamide, viscose, polyvinyl alcohol, urea-formaldehyde resin, melamine-formaldehyde resin, polyamide-polyamine-epichlorohydrin, etc., typically in a non-fibrous form. The above-mentioned resin components can function as paper strength enhancers for nonwoven fabrics. By using the above-mentioned resin components as required, the strength of the fiber sheet and the impregnation of the adhesive into the fiber sheet can be adjusted. The fiber sheet in the technology disclosed herein may also contain conventional additives in the field related to the manufacture of fiber sheets (e.g., nonwoven fabrics), such as retention aids, drainage agents, viscosity modifiers, and dispersants, as required.
[0040] <Adhesive layer>
[0041] (Base polymer)
[0042] The adhesive layer disclosed herein contains a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound as a base polymer. The monovinyl-substituted aromatic compound refers to a compound having a functional group having a vinyl group bonded to an aromatic ring. As a representative example of the aromatic ring, a benzene ring (which may be a benzene ring substituted by a functional group (such as an alkyl group) that does not have a vinyl group) can be cited. As specific examples of the monovinyl-substituted aromatic compound, styrene, α-methylstyrene, vinyltoluene, vinylxylene, etc. can be cited. As specific examples of the conjugated diene compound, 1,3-butadiene, isoprene, etc. can be cited. Such a block copolymer can be used alone or in combination of two or more for the base polymer.
[0043] In the A segment (hard segment) of the block copolymer, the copolymerization ratio of the monovinyl-substituted aromatic compound (two or more kinds of compounds may be used in combination) is preferably 70% by weight or more (more preferably 90% by weight or more, and may be substantially 100% by weight). In the B segment (soft segment) of the block copolymer, the copolymerization ratio of the conjugated diene compound (two or more kinds of compounds may be used in combination) is preferably 70% by weight or more (more preferably 90% by weight or more, and may be substantially 100% by weight). By using the block copolymer, a higher performance adhesive sheet can be achieved.
[0044] The block copolymer may be in the form of a diblock, a triblock, a radial, or a mixture thereof. In the triblock and radial, an A segment (e.g., a styrene block) is preferably disposed at the end of the polymer chain. This is because the A segment disposed at the end of the polymer chain is easily aggregated to form a domain, thereby forming a pseudo cross-linked structure to improve the cohesion of the adhesive.
[0045] As the block copolymer in the technology disclosed herein, from the viewpoint of the adhesive force (peel strength) to the adherend, a block copolymer having a diblock ratio of 30% by weight or more (more preferably 40% by weight or more, further preferably 50% by weight or more, particularly preferably 60% by weight or more, typically 65% by weight or more) can be preferably used. From the viewpoint of peel strength, a block copolymer having a diblock ratio of 70% by weight or more is particularly preferred. In addition, from the viewpoints of cohesion, a block copolymer having a diblock ratio of 90% by weight or less (more preferably 85% by weight or less, for example 80% by weight or less) can be preferably used. For example, a block copolymer having a diblock ratio of 60% to 85% by weight is preferred, and a block copolymer having a diblock ratio of 70% to 85% by weight (for example 70% to 80% by weight) is more preferably used.
[0046] In a preferred embodiment of the technology disclosed herein, the base polymer is a styrene block copolymer. For example, it is preferred that the base polymer includes at least one of a styrene-isoprene block copolymer and a styrene-butadiene block copolymer. In the styrene block copolymer contained in the adhesive, it is preferred that the ratio of styrene-isoprene block copolymer is more than 70% by weight, or the ratio of styrene-butadiene block copolymer is more than 70% by weight, or the total ratio of styrene-isoprene block copolymer and styrene-butadiene block copolymer is more than 70% by weight. In a preferred embodiment, substantially all (e.g., 95% to 100% by weight) of the styrene block copolymer is a styrene-isoprene block copolymer. In another preferred embodiment, substantially all (e.g., 95% to 100% by weight) of the styrene block copolymer is a styrene-butadiene block copolymer. According to such a composition, the effect of the technology disclosed herein can be better exerted.
[0047] The above-mentioned styrene block copolymer can be in the form of diblock, triblock, radial, mixtures thereof, etc. In triblock and radial, styrene blocks are preferably arranged at the end of the polymer chain. This is because the styrene blocks arranged at the end of the polymer chain are easily aggregated to form styrene domains, thereby forming a pseudo cross-linked structure to improve the cohesion of the adhesive. As for the styrene block copolymer used in the technology disclosed herein, from the viewpoint of the adhesive force (peel strength) to the adherend, it is preferred to use a styrene block copolymer with a diblock ratio of 30% by weight or more (more preferably 40% by weight or more, more preferably 50% by weight or more, particularly preferably 60% by weight or more, typically 65% by weight or more). It can also be a styrene block copolymer with a diblock ratio of 70% by weight or more (for example, 75% by weight or more). In addition, from the viewpoints of cohesion, it is preferred to use a styrene block copolymer with a diblock ratio of 90% by weight or less (more preferably 85% by weight or less, for example, 80% by weight or less). From the viewpoint of achieving a balanced balance between cohesion and low-temperature repulsion resistance by applying the technology disclosed herein, a styrene block copolymer having a diblock ratio of 60% to 85% by weight is preferred, and a styrene block copolymer having a diblock ratio of 70% to 85% by weight (e.g., 70% to 80% by weight) is more preferred.
[0048] The styrene content of the above-mentioned styrene block copolymer can be, for example, 5% to 40% by weight. From the viewpoint of cohesion, a styrene block copolymer having a styrene content of 10% by weight or more (more preferably greater than 10% by weight, for example, 12% by weight or more) is generally preferred. In addition, from the viewpoint of peel strength, the styrene content is preferably 35% by weight or less (typically 30% by weight or less, more preferably 25% by weight or less), particularly preferably 20% by weight or less (typically less than 20% by weight, for example, 18% by weight or less). From the viewpoint of better exerting the effect of the technology disclosed herein, a styrene block copolymer having a styrene content of 12% by weight or more and less than 20% by weight can be preferably used.
[0049] (Tackifying resin)
[0050] The PSA layer disclosed herein contains a tackifier resin in addition to the above-mentioned base polymer. The PSA layer preferably contains a tackifier resin having a softening point of less than 120°C and a tackifier resin having a softening point of 120°C or more as the tackifier resin.
[0051] The softening point of the tackifying resin described herein is defined as a value measured based on the softening point test method (ring and ball method) specified in JIS K5902 and JIS K2207. Specifically, the sample is quickly melted at the lowest possible temperature and carefully filled into a ring placed on a flat metal plate in a manner that does not form bubbles. After cooling, the raised portion is cut off from the plane containing the upper end of the ring using a slightly heated knife. Next, the support (ring stand) is placed in a glass container (heating bath) with a diameter of more than 85 mm and a height of more than 127 mm, and glycerin is injected to a depth of more than 90 mm. Next, a steel ball (diameter of 9.5 mm, weight of 3.5 g) and a ring filled with the sample are immersed in glycerin in a non-contact manner, and the temperature of the glycerin is maintained at 20°C ± 5°C for 15 minutes. Next, the steel ball is placed in the center of the surface of the sample in the ring and is placed in a fixed position on the support. Next, keep the distance from the upper end of the ring to the glycerin surface at 50 mm, place a thermometer so that the center of the mercury ball of the thermometer is at the same height as the center of the ring, and heat the container. Make the flame of the Bunsen burner used for heating contact the center of the bottom of the container and the middle of the edge to heat evenly. It should be noted that the rate of increase in the bath temperature after reaching 40°C after the start of heating must be 5.0±0.5°C per minute. Read the temperature when the sample gradually softens and flows down from the ring and finally contacts the bottom plate, and use it as the softening point. Perform the softening point measurement of more than 2 times at the same time, and use the average value.
[0052] The tackifier resin having a softening point of less than 120°C and the tackifier resin having a softening point of more than 120°C can be independently selected from various well-known tackifier resins such as petroleum resins, styrene resins, coumarone-indene resins, terpene resins, modified terpene resins, rosin resins, rosin derivative resins, ketone resins, etc., and the tackifier resin having a softening point that satisfies the conditions can be appropriately selected and used.
[0053] Examples of petroleum resins include aliphatic (C5) petroleum resins, aromatic (C9) petroleum resins, aliphatic / aromatic copolymer (C5 / C9) petroleum resins, and hydrogenated products thereof (e.g., alicyclic petroleum resins obtained by hydrogenating aromatic petroleum resins).
[0054] Examples of styrene-based resins include styrene-based resins having a homopolymer of styrene as a main component, styrene-based resins having a homopolymer of α-methylstyrene as a main component, styrene-based resins having a homopolymer of vinyltoluene as a main component, styrene-based resins having a copolymer containing two or more of styrene, α-methylstyrene and vinyltoluene in a monomer composition as a main component (for example, an α-methylstyrene / styrene copolymer resin having an α-methylstyrene / styrene copolymer as a main component), and the like.
[0055] As the coumarone-indene resin, a resin containing coumarone and indene as monomer components constituting the backbone (main chain) of the resin can be used. Examples of monomer components other than coumarone and indene that can be contained in the backbone of the resin include styrene, α-methylstyrene, methylindene, vinyltoluene, and the like.
[0056] Examples of terpene resins include α-pinene polymers, β-pinene polymers, dipentene polymers, etc. Examples of modified terpene resins include those obtained by modifying the above terpene resins (phenol modification, styrene modification, hydrogenation modification, hydrocarbon modification, etc.). Specifically, terpene phenol resins, styrene-modified terpene resins, hydrogenated terpene resins, etc. can be exemplified.
[0057] The above-mentioned "terpene phenol resin" refers to a polymer containing a terpene residue and a phenol residue, and is a concept including a copolymer of a terpene and a phenol compound (terpene-phenol copolymer resin) and a homopolymer or copolymer of a terpene (terpene resin, typically an unmodified terpene resin) modified with phenol (phenol-modified terpene resin). Preferred examples of terpenes constituting the above-mentioned terpene phenol resin include monoterpenes such as α-pinene, β-pinene, and limonene (including d-form, l-form, and d / l-form (pine oil)).
[0058] Specific examples of rosin-based resins include unmodified rosins (raw rosins) such as gum rosin, wood rosin, and tall oil rosin; modified rosins (hydrogenated rosin, disproportionated rosin, polymerized rosin, and other chemically modified rosins) obtained by modifying these unmodified rosins by hydrogenation, disproportionation, polymerization, etc. In addition, examples of rosin derivative resins include rosin esters such as those obtained by esterifying unmodified rosin with alcohols (i.e., esters of rosin), and those obtained by esterifying modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) with alcohols (i.e., esters of modified rosin); unsaturated fatty acid-modified rosins obtained by modifying unmodified rosin or modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.) with unsaturated fatty acids; and rosin esters obtained by modifying rosin with unsaturated fatty acids. unsaturated fatty acid modified rosin esters obtained; rosin alcohols obtained by reducing the carboxyl groups in unmodified rosin, modified rosin (hydrogenated rosin, disproportionated rosin, polymerized rosin, etc.), unsaturated fatty acid modified rosins or unsaturated fatty acid modified rosin esters; metal salts of rosins (especially rosin esters) such as unmodified rosin, modified rosin, various rosin derivatives, etc.; rosin phenol resins obtained by adding phenol to rosins (unmodified rosin, modified rosin, various rosin derivatives, etc.) using an acid catalyst and thermally polymerizing them; etc.
[0059] As a preferred embodiment, the adhesive layer contains one or more terpene phenol resins. For example, the proportion of terpene phenol resin in the total amount of tackifying resin can be, for example, 15% by weight or more, preferably 25% by weight or more, 30% by weight or more, or 35% by weight or more. In some embodiments, the above proportion can be 45% by weight or more, or 55% by weight or more. In addition, the proportion of terpene phenol resin in the total amount of tackifying resin can be, for example, 90% by weight or less, preferably 80% by weight or less, 70% by weight or less, 60% by weight or less, or 50% by weight or less.
[0060] When the adhesive layer contains a terpene-phenol resin as a tackifying resin, the content of the terpene-phenol resin is appropriately 5 parts by weight or more, preferably 10 parts by weight or more (e.g., greater than 10 parts by weight), and more preferably 15 parts by weight or more, relative to 100 parts by weight of the base polymer. In addition, the content of the terpene-phenol resin in the adhesive layer is appropriately 70 parts by weight or less, preferably 60 parts by weight or less, and more preferably 50 parts by weight or less, relative to 100 parts by weight of the base polymer.
[0061] (Tackifying resin T H )
[0062] In the technology disclosed herein, the tackifier resin preferably contains a tackifier resin having a softening point of 120° C. or higher (hereinafter, sometimes referred to as “tackifier resin T H ”). From the perspective of resilience resistance and high temperature cohesion, the tackifying resin T H The softening point of the tackifier resin T is preferably 125°C or higher, more preferably 130°C or higher, and further preferably 135°C or higher (for example, 140°C or higher). H The softening point is usually appropriately 200°C or lower, preferably 180°C or lower, more preferably 170°C or lower (eg 160°C or lower).
[0063] As tackifying resin T H For example, one or more of the above-mentioned petroleum resins, styrene resins, coumarone-indene resins, modified terpene resins, rosin resins, rosin derivative resins, ketone resins, etc. can be used. Among them, terpene phenol resins, rosin phenol resins, polymerized rosin, and esters of polymerized rosin are preferred.
[0064] As a preferred embodiment, one or more terpene phenol resins can be used as the tackifying resin T. H The softening point of the terpene-phenol resin used may be, for example, 125°C or more. From the viewpoints of heat resistance and cohesion, it is preferably 130°C or more, 135°C or more, or 140°C or more. The softening point of the terpene-phenol resin may be, for example, 200°C or less. From the viewpoints of adhesion and compatibility, it is preferably 180°C or less, 170°C or less, or 160°C or less.
[0065] In some embodiments, the tackifying resin T H 25 wt % or more (preferably 30 wt % or more, more preferably 50 wt % or more, for example 60 wt % or more) of the terpene phenol resin may be set. H The amount of terpene phenol resin in the tackifier resin may be, for example, about 85% by weight or less, or about 75% by weight or less. H The amount of the terpene phenol resin in the tackifier resin may be, for example, 70% by weight or more, 80% by weight or more, or 90% by weight or more. H Substantially all (for example, 95% to 100% by weight, further 99% to 100% by weight) of the terpene-phenol resin may be present.
[0066] The technology disclosed herein can preferably contain a tackifier resin T having a hydroxyl value of 80 mgKOH / g or more (e.g., 90 mgKOH / g or more). H As tackifying resin T HHereinafter, a tackifying resin T having a hydroxyl value of 80 mgKOH / g or more (for example, 90 mgKOH / g or more) may be used. H Recorded as "tackifying resin T HO1 ". Tackifying resin T HO1 The hydroxyl value is typically 200 mgKOH / g or less, preferably 180 mgKOH / g or less, for example 160 mgKOH / g or less. HO1 By using an adhesive of a higher performance, a higher performance adhesive sheet can be realized. For example, a higher level of cohesiveness and other properties (such as low temperature repulsion resistance, etc.) can be achieved.
[0067] Here, as the value of the hydroxyl value of the tackifier resin in this specification, there can be adopted a value measured by the potentiometric titration method specified in JIS K0070: 1992. The specific measurement method is as follows.
[0068] [Method for measuring hydroxyl value]
[0069] 1. Reagents
[0070] (1) As the acetylating agent, a reagent obtained by taking about 12.5 g (about 11.8 mL) of acetic anhydride, adding pyridine thereto to make a total amount of 50 mL, and stirring thoroughly was used; or a reagent obtained by taking about 25 g (about 23.5 mL) of acetic anhydride, adding pyridine thereto to make a total amount of 100 mL, and stirring thoroughly was used.
[0071] (2) As a measurement reagent, a 0.5 mol / L potassium hydroxide ethanol solution was used.
[0072] (3) In addition, toluene, pyridine, ethanol and distilled water are prepared.
[0073] 2. Operation
[0074] (1) Accurately weigh about 2 g of the sample into a flat-bottom flask, add 5 mL of the acetylating agent and 10 mL of pyridine, and install an air cooling tube.
[0075] (2) The flask was heated in a bath at 100°C for 70 minutes, then cooled naturally, 35 mL of toluene was added from the top of the cooling tube as a solvent and stirred, and then 1 mL of distilled water was added and stirred to decompose acetic anhydride. In order to completely decompose, the flask was heated in the bath again for 10 minutes and cooled naturally.
[0076] (3) The cooling tube was washed with 5 mL of ethanol and removed. Then, 50 mL of pyridine was added as a solvent and stirred.
[0077] (4) Using a full-volume pipette, add 25 mL of 0.5 mol / L potassium hydroxide ethanol solution.
[0078] (5) Potentiometric titration was performed using 0.5 mol / L potassium hydroxide ethanol solution. The inflection point of the obtained titration curve was taken as the end point.
[0079] (6) In a blank test, the above (1) to (5) are carried out without adding a sample.
[0080] 3. Calculation
[0081] The hydroxyl value was calculated by the following formula.
[0082] Hydroxyl value (mgKOH / g) = [(BC) × f × 28.05] / S + D
[0083] Here,
[0084] B: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the blank test (mL),
[0085] C: The amount of 0.5 mol / L potassium hydroxide ethanol solution used in the sample (mL),
[0086] f: coefficient of 0.5 mol / L potassium hydroxide ethanol solution,
[0087] S: weight of sample (g),
[0088] D: Acid value,
[0089] 28.05: 1 / 2 of the molecular weight of potassium hydroxide, 56.11.
[0090] As tackifying resin T HO1 In particular, the tackifier resins having a hydroxyl value of a predetermined value or more among the above-mentioned various tackifier resins can be used alone or in appropriate combination. In a preferred embodiment, at least a terpene phenol resin is used as the tackifier resin. HO1 Terpene phenol resin is preferred because the hydroxyl value can be arbitrarily controlled by the copolymerization ratio of phenol. HO1 The proportion of the tackifier resin T is preferably about 50% by weight or more, preferably 80% by weight or more, and more preferably 90% by weight or more. HO1 Substantially all (for example, 95% to 100% by weight, further 99% to 100% by weight) of the terpene-phenol resin may be present.
[0091] The technology disclosed herein is to use a tackifying resin T HO1 When the adhesive layer is implemented, the tackifying resin T HO1The proportion of the total tackifying resin is not particularly limited. The above proportion may be, for example, 10% by weight or more, preferably 15% by weight or more, more preferably 20% by weight or more, or 25% by weight or more. In addition, in some embodiments, from the viewpoints of adhesion, compatibility, etc., the above proportion may be, for example, 70% by weight or less, 60% by weight or less, 50% by weight or less, or 40% by weight or less.
[0092] The technology disclosed herein can preferably be used in that the adhesive layer contains a tackifying resin T having a hydroxyl value of greater than or equal to 40 mgKOH / g and less than 80 mgKOH / g. H Hereinafter, a tackifying resin T having a hydroxyl value of 40 mgKOH / g or more and less than 80 mgKOH / g may be used. H Recorded as "tackifying resin T HO2 ". Tackifying resin T HO2 The hydroxyl value of the tackifying resin T may be 45 mgKOH / g or more, or 50 mgKOH / g or more. HO2 The hydroxyl value may be 75 mgKOH / g or less, or 70 mgKOH / g or less.
[0093] As tackifying resin T HO2 For example, the tackifying resins satisfying the specified hydroxyl value can be used alone or in appropriate combination. HO2 , at least terpene phenol resin is used. Terpene phenol resin is used as a tackifying resin T HO2 The proportion of the tackifier resin T is preferably about 50% by weight or more, preferably 80% by weight or more, and more preferably 90% by weight or more. HO2 Substantially all (for example, 95% to 100% by weight, further 99% to 100% by weight) of the terpene-phenol resin may be present.
[0094] The technology disclosed herein uses a tackifying resin T HO2 When the adhesive layer is implemented, the tackifying resin T HO2 The proportion of the total tackifying resin is not particularly limited. The above proportion may be, for example, 10% by weight or more, preferably 15% by weight or more, more preferably 20% by weight or more, or 25% by weight or more. In addition, in some embodiments, from the perspective of the cohesiveness of the adhesive, the above proportion may be, for example, 70% by weight or less, 60% by weight or less, 50% by weight or less, or 40% by weight or less.
[0095] In some preferred embodiments, a tackifying resin T may be used in combination. HO1 and tackifying resin T HO2In the method described, T HO1 With T HO2 The relationship between the usage amounts can be, for example, such that the weight ratio (T HO1 :T HO2 ) is set in the range of 1:5 to 5:1 so that the weight ratio (T HO1 :T HO2 ) is appropriately set in the range of 1:3 to 3:1 (e.g., 1:2 to 2:1). As a preferred embodiment, T HO1 、T HO2 All of them are terpene phenol resins.
[0096] In one embodiment of the technology disclosed herein, the tackifier resin T H It may contain a tackifying resin T having an aromatic ring and a hydroxyl value of less than 40 mgKOH / g H Hereinafter, a tackifier resin T having an aromatic ring and a hydroxyl value of less than 40 mgKOH / g may be used. H Recorded as "tackifying resin T HR1 ". Tackifying resin T HR1 The hydroxyl value is preferably less than 30 mgKOH / g, more preferably less than 10 mgKOH / g, less than 5 mgKOH / g, or less than 3 mgKOH / g. In some embodiments, it is preferred to use a tackifying resin T having a hydroxyl value of less than 1 mgKOH / g or no hydroxyl group detected. HR1 .
[0097] Examples of tackifier resins having an aromatic ring include the above-mentioned aromatic petroleum resins, aliphatic / aromatic copolymerized petroleum resins, styrene resins, coumarone-indene resins, styrene-modified terpene resins, phenol-modified terpene resins, rosin phenol resins, etc. Among these, a tackifier resin having a softening point of 120° C. or more (preferably 130° C. or more, for example 135° C. or more) and satisfying any of the above-mentioned hydroxyl values can be used as the tackifier resin T. HR1 As a preferred tackifying resin T HR1 Examples of the tackifier resin include aromatic petroleum resins and styrene resins (e.g., α-methylstyrene / styrene copolymer resins). It should be noted that the technology disclosed herein can also be used in which the adhesive layer is substantially free of tackifier resin T HR1 way to implement it.
[0098] In another embodiment of the adhesive disclosed herein, the tackifying resin T H The tackifier resin T may contain an aromatic ring and substantially no isoprene unit, terpene skeleton, or rosin skeleton. H Hereinafter, such a tackifying resin T H Recorded as "tackifying resin T HR2Here, the tackifying resin T HR2 Substantially free of isoprene units, terpene skeletons and rosin skeletons means that these structural parts (i.e., isoprene units, terpene skeletons and rosin skeletons) are contained in the tackifying resin T. HR2 The total proportion of isoprene units, terpene skeletons and rosin skeletons in the tackifying resin T is less than 10% by weight (more preferably less than 8% by weight, further preferably less than 5% by weight, for example less than 3% by weight). The above proportion can be 0% by weight. It should be noted that the isoprene units, terpene skeletons and rosin skeletons in the tackifying resin T HR2 The proportion of can be measured by, for example, NMR (nuclear magnetic resonance spectroscopy).
[0099] Examples of tackifier resins having an aromatic ring and substantially free of isoprene units, terpene skeletons, and rosin skeletons include the above-mentioned aromatic petroleum resins, aliphatic / aromatic copolymerized petroleum resins, styrene resins, coumarone-indene resins, etc. Among these, tackifier resins having a softening point of 120° C. or higher (preferably 130° C. or higher, for example 135° C. or higher) can be used as tackifier resins. HR2 Among them, the preferred tackifying resin T HR2 Examples of the tackifier resin include aromatic petroleum resins and styrene resins (e.g., α-methylstyrene / styrene copolymer resins). HR2 For example, a tackifying resin T having a hydroxyl value of less than 40 mgKOH / g (more preferably less than 30 mgKOH / g, further preferably less than 10 mgKOH / g, for example less than 5 mgKOH / g or less than 3 mgKOH / g) can be preferably used. HR2 Therefore, as the tackifying resin T in the technology disclosed herein HR2 For example, it is preferred to use a tackifying resin T HR1 Similarly, as the tackifying resin T in the technology disclosed herein HR1 For example, it is preferred to use a tackifying resin T HR2 It should be noted that the technology disclosed herein can also be used in which the adhesive layer does not substantially contain a tackifying resin T HR2 way to implement it.
[0100] From the viewpoint of improving cohesion, the amount of tackifier resin T relative to 100 parts by weight of the base polymer is H The total amount (i.e., the total amount of the tackifier resin having a softening point of 120°C or more) is appropriately set to 20 parts by weight or more, preferably 30 parts by weight or more, and more preferably 35 parts by weight or more. The technology disclosed herein can preferably be used with a tackifier resin T relative to 100 parts by weight of the base polymer. HThe total amount of the base polymer is 40 parts by weight or more (e.g., 50 parts by weight or more). H The content of can be set to, for example, 100 parts by weight or less, and is appropriately set to 90 parts by weight or less, preferably 80 parts by weight or less, from the viewpoint of adhesive force and compatibility.
[0101] From the viewpoint of improving cohesion, the tackifier resin T H It is appropriate to set the proportion of the total amount of tackifying resin to be about 20% by weight or more, preferably 30% by weight or more, more preferably 40% by weight or more, 50% by weight or more, or 60% by weight or more. In addition, the above proportion can be set to, for example, 95% by weight or less, and from the viewpoint of improving the adhesive force, it is advantageous to set it to 85% by weight or less, and it can be 75% by weight or less, 70% by weight or less, or 65% by weight or less.
[0102] (Tackifying resin T L )
[0103] In the technology disclosed herein, the above-mentioned tackifying resin is preferably in addition to the tackifying resin T H In addition, it also contains a tackifier resin having a softening point of less than 120°C (hereinafter sometimes referred to as "tackifier resin T L ”) By using a tackifying resin T in combination H and tackifying resin T L , and both adhesiveness and cohesion can be balanced. Thus, a PSA sheet showing high peel strength can be appropriately realized.
[0104] Tackifying resin T L The lower limit of the softening point is not particularly limited. Generally, a tackifier resin having a softening point of 40°C or more (typically 60°C or more) can be preferably used. From the perspective of achieving both high levels of adhesion and cohesion, a tackifier resin T having a softening point of 80°C or more (more preferably 100°C or more) and less than 120°C can be preferably used. L Among them, it is preferred to use a tackifier resin T having a softening point of 110°C or more and less than 120°C. L .
[0105] As tackifying resin T L As for the above-mentioned various tackifying resins (petroleum resin, styrene resin, coumarone-indene resin, terpene resin, modified terpene resin, rosin resin, rosin derivative resin, ketone resin, etc.) having a softening point of less than 120°C can be used alone or in appropriate combination.
[0106] The technology disclosed herein can preferably include at least one of a petroleum resin and a terpene resin as the above-mentioned tackifier resin T L For example, the tackifying resin T L The main component (i.e., the tackifying resin T L The composition of the tackifying resin T is preferably a petroleum resin composition, a terpene resin composition, a combination of a petroleum resin and a terpene resin, etc. From the viewpoint of adhesion and compatibility, the tackifying resin T is preferably L The main component is a terpene resin (for example, β-pinene polymer). L Substantially all (for example, 95% by mass or more) of the resin may be terpene resin.
[0107] From the viewpoint of improving cohesion, the amount of tackifier resin T relative to 100 parts by weight of the base polymer is L The total amount of the tackifier resin T (i.e., the total amount of the tackifier resin having a softening point of less than 120°C) is appropriately set to 50 parts by weight or less, preferably 40 parts by weight or less, and may be 35 parts by weight or less. L The content can be, for example, 5 parts by weight or more. From the viewpoint of improving adhesion and impregnation into the fiber sheet, it is preferably set to 10 parts by weight or more, 15 parts by weight or more, 20 parts by weight or more, or 25 parts by weight or more.
[0108] In the technology disclosed herein, the total amount of the tackifying resin relative to 100 parts by mass of the base polymer is not particularly limited. From the viewpoint of taking into account both adhesion and cohesion in a balanced manner, the total amount of the above-mentioned tackifying resin is usually more than 20 parts by mass, preferably more than 30 parts by mass, more preferably more than 40 parts by mass (for example, more than 50 parts by mass). In addition, from the viewpoints such as low temperature characteristics (such as low temperature peel strength), the content of the tackifying resin relative to 100 parts by mass of the base polymer is usually less than 200 parts by mass, preferably less than 150 parts by mass, more preferably less than 120 parts by mass (for example, less than 100 parts by mass). It should be noted that the total amount of the above-mentioned tackifying resin can be tackifying resin T H Total amount and tackifying resin T L The total amount of .
[0109] (Isocyanate compound)
[0110] The adhesive composition disclosed herein may also contain an isocyanate compound. Isocyanate compounds can improve the cohesiveness of the adhesive, and contribute to the realization of an adhesive sheet showing higher peel strength. As isocyanate compounds, polyfunctional isocyanates (referring to compounds having an average of more than 2 isocyanate groups per molecule, including compounds having an isocyanurate structure) can be preferably used. As the polyfunctional isocyanate, one or more of the various isocyanate compounds (polyisocyanates) selected from having more than 2 isocyanate groups in one molecule can be used. As examples of the polyfunctional isocyanates, aliphatic polyisocyanates, alicyclic polyisocyanates, aromatic polyisocyanates, etc. can be cited.
[0111] Specific examples of aliphatic polyisocyanates include: 1,2-ethylene diisocyanate; tetramethylene diisocyanates such as 1,2-tetramethylene diisocyanate, 1,3-tetramethylene diisocyanate, and 1,4-tetramethylene diisocyanate; hexamethylene diisocyanates such as 1,2-hexamethylene diisocyanate, 1,3-hexamethylene diisocyanate, 1,4-hexamethylene diisocyanate, 1,5-hexamethylene diisocyanate, 1,6-hexamethylene diisocyanate, and 2,5-hexamethylene diisocyanate; 2-methyl-1,5-pentane diisocyanate, 3-methyl-1,5-pentane diisocyanate, and lysine diisocyanate.
[0112] Specific examples of alicyclic polyisocyanates include isophorone diisocyanate; cyclohexyl diisocyanates such as 1,2-cyclohexyl diisocyanate, 1,3-cyclohexyl diisocyanate, and 1,4-cyclohexyl diisocyanate; cyclopentyl diisocyanates such as 1,2-cyclopentyl diisocyanate and 1,3-cyclopentyl diisocyanate; hydrogenated xylylene diisocyanate, hydrogenated toluene diisocyanate, hydrogenated diphenylmethane diisocyanate, hydrogenated tetramethylxylene diisocyanate, and 4,4'-dicyclohexylmethane diisocyanate.
[0113] Specific examples of the aromatic polyisocyanates include 2,4-toluene diisocyanate, 2,6-toluene diisocyanate, 4,4'-diphenylmethane diisocyanate, 2,4'-diphenylmethane diisocyanate, 2,2'-diphenylmethane diisocyanate, 4,4'-diphenylether diisocyanate, 2-nitrobiphenyl-4,4'-diisocyanate, 2,2'-diphenylpropane-4,4'-diisocyanate, '-diisocyanate, 3,3'-dimethyldiphenylmethane-4,4'-diisocyanate, 4,4'-diphenylpropane diisocyanate, m-phenylene diisocyanate, p-phenylene diisocyanate, 1,4-naphthalene diisocyanate, 1,5-naphthalene diisocyanate, 3,3'-dimethoxybiphenyl-4,4'-diisocyanate, xylylene-1,4-diisocyanate, xylylene-1,3-diisocyanate, etc.
[0114] As a preferred isocyanate compound, a polyfunctional isocyanate having an average of 3 or more isocyanate groups per molecule can be exemplified. The trifunctional or higher isocyanate can be a polymer (typically a dimer or trimer) of a difunctional or trifunctional or higher isocyanate, a derivative (for example, an addition reaction product of a polyol and two or more molecules of a polyfunctional isocyanate), a polymer, etc. For example, polyfunctional isocyanates such as a dimer or trimer of diphenylmethane diisocyanate, an isocyanurate form of hexamethylene diisocyanate (a trimer adduct of an isocyanurate structure), a reaction product of trimethylolpropane and toluene diisocyanate, a reaction product of trimethylolpropane and hexamethylene diisocyanate, polymethylene polyphenyl isocyanate, a polyether polyisocyanate, and a polyester polyisocyanate can be cited. Examples of commercially available products of the polyfunctional isocyanate include "DURANATE TPA-100" manufactured by Asahi Kasei Chemicals Corporation, "Coronate L" manufactured by Tosoh Corporation, "Coronate HL" manufactured by Tosoh Corporation, "Coronate HK" manufactured by Tosoh Corporation, "Coronate HX" manufactured by Tosoh Corporation, and "Coronate 2096" manufactured by Tosoh Corporation.
[0115] When an isocyanate compound is used, there is no particular restriction on its usage amount, for example, it can be set to be greater than 0 weight part and less than or equal to 10 weight parts (typically 0.01 weight part to 10 weight parts) relative to 100 weight parts of the base polymer. Generally, it is appropriate to set the usage amount of the isocyanate compound relative to 100 weight parts of the base polymer to 0.1 weight part to 10 weight parts, preferably 0.1 weight part to 5 weight parts (typically 0.3 weight part to 3 weight parts, for example 0.5 weight part to 1 weight part). By using the isocyanate compound within the above range, an adhesive sheet with excellent performance balance can be achieved in particular.
[0116] (Other ingredients)
[0117] In the range that does not significantly impair the effect of the present invention, the adhesive layer in the technology disclosed herein can contain one or more rubber-like polymers other than the base polymer as needed. The rubber-like polymer can be various polymers such as rubber, acrylic, polyester, urethane, polyether, polysiloxane, polyamide, fluorine-containing type, etc. known in the field of adhesives. The technology disclosed herein can preferably be implemented in a manner that the above-mentioned adhesive layer does not substantially contain a rubber-like polymer other than the base polymer (for example, a manner in which the content is 0 to 1 parts by weight relative to every 100 parts by weight of the base polymer).
[0118] The adhesive layer in the disclosed technology can contain various additives conventional in the field of adhesive such as leveling agent, crosslinking agent, crosslinking aid, plasticizer, softener, filler, colorant (pigment, dye, etc.), antistatic agent, antioxidant, ultraviolet absorber, antioxidant, light stabilizer as needed. About such various additives, existing known additives can be used by conventional methods. The adhesive disclosed in this can preferably be implemented in a manner that does not substantially contain liquid rubbers such as polybutene (for example, the content relative to every 100 parts by weight of base polymer is less than 1 part by weight, can be 0 parts by weight).
[0119] In a preferred embodiment, the adhesive layer may be composed of a total amount of the base polymer and the tackifying resin accounting for 90% by weight or more of the total weight of the adhesive (i.e., the weight of the adhesive layer composed of the adhesive). For example, it may be preferred that the total amount of the base polymer and the tackifying resin is 90% to 99.8% by weight (typically, 95% to 99.5% by weight) of the total weight of the adhesive.
[0120] In another preferred embodiment, the adhesive composition may be a composition that does not substantially contain a chelate compound. Here, the chelate compound, for example, refers to a chelate compound of an oxide of an alkaline earth metal and a resin (alkylphenol resin, etc.) having a functional group (hydroxyl, methylol, etc.) that the oxide can coordinate. The technology disclosed herein may preferably be implemented in a manner that the adhesive composition does not contain such a chelate compound at all or the chelate compound contains a proportion of less than 1% by weight. According to the described method, an adhesive sheet with better adhesion can be achieved.
[0121] (Adhesive composition)
[0122] The adhesive layer in the technology disclosed herein can be a layer formed by an adhesive composition comprising a base polymer and a tackifying resin. There is no particular limitation on the form of the adhesive composition disclosed herein, and for example, it can be an adhesive composition in the form of an adhesive (adhesive component) of the composition described above in an organic solvent (solvent-type), an adhesive composition in the form of an adhesive dispersed in an aqueous solvent (water-dispersible type, typically an aqueous emulsion type), a hot-melt adhesive composition, etc. From the perspective of the impregnation and adhesion of the fiber sheet, in some embodiments, an adhesive layer formed by a solvent-type adhesive composition is preferred.
[0123] The solvent-based adhesive composition is typically prepared in the form of a solution containing the above-mentioned components in an organic solvent. The above-mentioned organic solvent can be appropriately selected from well-known or commonly used organic solvents. For example, any one solvent or a mixed solvent of two or more selected from aromatic compounds such as toluene and xylene (typically aromatic hydrocarbons); acetates such as ethyl acetate and butyl acetate; aliphatic hydrocarbons or alicyclic hydrocarbons such as hexane, cyclohexane, and methylcyclohexane; halogenated alkanes such as 1,2-dichloroethane; ketones such as methyl ethyl ketone and acetylacetone; etc. can be used. There are no particular restrictions. Generally, it is appropriate to prepare the above-mentioned solvent-based adhesive composition to have a solid content (NV) of 30% to 65% by weight (for example, 40% to 55% by weight). When the NV is too low, the manufacturing cost tends to increase, and when the NV is too high, sometimes the operability such as coating property decreases.
[0124] As a method for obtaining an adhesive sheet from an adhesive composition, various methods known in the art can be applied. For example, a method (direct method) in which an adhesive composition is directly applied (typically coated) on a fiber sheet and dried to form an adhesive layer can be preferably adopted. In addition, a method (transfer method) in which an adhesive layer is formed on a surface with good releasability (e.g., the surface of a release liner) by applying the adhesive composition and drying the surface and the adhesive layer is transferred to the fiber sheet can also be adopted.
[0125] The coating of the adhesive composition can be carried out using, for example, a gravure roll coater, a reverse roll coater, a roll lick coater, a dip roll coater, a bar coater, a knife coater, a spray coater, or other known or commonly used coaters. From the perspective of promoting cross-linking reaction and improving manufacturing efficiency, it is preferred to dry the adhesive composition under heating. Usually, for example, a drying temperature of about 40°C to about 150°C (typically about 40°C to about 120°C, for example, about 50°C to about 120°C, and further about 70°C to about 100°C) can be preferably used. There is no particular restriction on the drying time, which can be set to about tens of seconds to about several minutes (for example, within about 5 minutes, preferably about 30 seconds to 2 minutes). Then, an additional drying process can be provided as needed. The adhesive layer is typically formed continuously, but it can also be formed into regular or irregular patterns such as dots and stripes according to the purpose and use. In some embodiments, the adhesive layer in the technology disclosed herein is preferably formed in the form of a layer that is substantially free of bubbles. Here, the fact that the pressure-sensitive adhesive layer contains substantially no bubbles means that the ratio of the volume of bubbles to the apparent volume of the pressure-sensitive adhesive layer at 25° C. is less than 3% by volume (typically less than 1% by volume).
[0126] (Thickness of adhesive layer)
[0127] In the adhesive sheet disclosed herein, the thickness of the adhesive layer is preferably greater than 100 μm and less than 190 μm. By having an adhesive layer having a thickness greater than 100 μm and laminating the adhesive layer on a fiber sheet, high peel strength can be exerted for both smooth and rough surfaces. In addition, by having an adhesive layer having a thickness less than 190 μm, an adhesive sheet having a peel strength on a rough surface (peel strength on a rough surface) equal to or higher than a peel strength on a smooth surface (peel strength on a smooth surface) can be appropriately achieved. In some embodiments, the ratio of the above-mentioned peel strengths (rough surface / adhesive surface) is, for example, greater than 1.0, preferably greater than 1.0, and more preferably greater than 1.05. The peel strength on a rough surface is measured by using a felt (manufactured by Ambik Co., Ltd., trade name "Himelon SP30B") as an adherend and using the method described in the embodiments described later. The peel strength on a smooth surface is measured by using an ABS plate as an adherend and using the method described in the embodiments described later.
[0128] It should be noted that, in the case of an adhesive sheet having an adhesive layer on both sides of a fiber sheet, the thickness of the adhesive layer refers to the thickness of each single-sided adhesive layer. The thickness of the adhesive layer (first adhesive layer) stacked on the first side of the fiber sheet and the thickness of the adhesive layer (second adhesive layer) stacked on the second side of the fiber sheet can be the same or different. Similarly, the composition of the first adhesive layer (for example, the type and amount of tackifying resin, the type and amount of crosslinking agent when a crosslinking agent is used, etc.) can be the same or different from the composition of the second adhesive layer. The adhesive sheet disclosed herein can preferably be implemented in a manner that the first adhesive layer and the second adhesive layer are of the same composition (for example, formed by the same adhesive composition) and of the same thickness. The adhesive sheet of such a composition can be used without distinguishing between the front and back, and is therefore easy to use.
[0129] <Adhesive Sheet>
[0130] The total thickness of the adhesive sheet disclosed herein is typically greater than 100 μm, for example, it can be set to be greater than 100 μm and less than 2000 μm. In some embodiments, from the perspective of non-adhesive residual properties, the total thickness of the adhesive sheet can be, for example, less than 1000 μm, less than 500 μm, less than 400 μm, or less than 350 μm. In addition, the total thickness of the adhesive sheet can be, for example, greater than 150 μm, and from the perspective of improving peel strength, it is preferably greater than 180 μm, greater than 200 μm, greater than 240 μm, or greater than 280 μm.
[0131] In addition, the total thickness of the adhesive sheet disclosed herein is typically 1.1 times or more of the thickness of the fiber sheet contained in the adhesive sheet, for example, it can be 1.5 times or more. From the viewpoint of improving peel strength, it is advantageous for the total thickness of the adhesive sheet to be 3.0 times or more of the thickness of the fiber sheet, preferably 4.0 times or more, and more preferably 4.5 times or more (for example, about 4.5 times to about 6.5 times). In some embodiments, the total thickness of the adhesive sheet can be 7.0 times or more of the thickness of the fiber sheet, 10 times or more, 12 times or more (for example, about 12 times to about 25 times), or 15 times or more. The total thickness of the adhesive sheet can be, for example, 50 times or less of the thickness of the fiber sheet. In some embodiments, from the viewpoint of non-adhesive residue, the total thickness of the adhesive sheet can be 30 times or less of the thickness of the fiber sheet, 25 times or less, 20 times or less, 16 times or less, 11 times or less, or 8.0 times or less.
[0132] There is no particular restriction on the 180 degree peel strength of the adhesive sheet disclosed herein to the stainless steel plate, and 20N / 20mm or more is appropriate, preferably 30N / 20mm or more, more preferably 35N / 20mm or more, and further preferably 40N / 20mm or more. The adhesive sheet disclosed herein may also be preferably implemented in a manner such that the above 180 degree peel strength is 44N / 20mm or more, 47N / 20mm or more, or 50N / 20mm or more. In addition, the above 180 degree peel strength is typically 100N / 20mm or less, and from the viewpoint of suppressing the adhesive residue (paste residue) on the adherend surface after peeling, it is preferably 80N / 20mm or less, 70N / 20mm or less, or 65N / 20mm or less.
[0133] Here, the 180-degree peel strength of the adhesive sheet to the stainless steel plate can be understood in the following way: it is pressed on the stainless steel plate (more specifically, the SUS304BA plate) as the adherend, placed in an environment of 23°C and 50% RH for 30 minutes, and then the 180° peeling adhesion is measured under the conditions of a peeling angle of 180 degrees and a tensile speed of 300 mm / min according to JIS Z 0237. During the measurement, it is preferred to stick a suitable lining material (for example, a PET film with a thickness of 25 μm) on the back of the adhesive sheet (the surface on the opposite side of the side pasted on the adherend) for reinforcement. The adhesive sheet disclosed herein can be peeled off at the interface between the adherend and the adhesive sheet without leaving the adhesive on the SUS304BA plate as the adherend in the above-mentioned 180-degree peel strength measurement. According to such an adhesive sheet, it is possible to appropriately take into account the high peel strength suitable for fixing and joining components constituting various products and the good non-adhesive residue when separating the component and the adhesive sheet when the above-mentioned component is reused.
[0134] The adhesive sheet disclosed herein can be satisfactorily used for joining or fixing components contained in various products such as office automation (OA) equipment, home appliances, and automobiles, typically in the form of a double-sided adhesive sheet comprising a fiber sheet, an adhesive layer (first adhesive layer) laminated on the first side of the fiber sheet, and an adhesive layer (second adhesive layer) laminated on the second side. Since the adhesive sheet disclosed herein can be firmly bonded to either a smooth surface or a rough surface, it is particularly suitable for use in bonding a smooth surface of a component to a rough surface of another component.
[0135] It should be noted that, in this specification, a smooth surface typically refers to a surface with a surface roughness Sz less than 100 μm. The adhesive sheet disclosed herein can preferably be used in a manner in which an adhesive surface is crimped onto a surface (i.e., a smooth surface) with a surface roughness Sz less than 100 μm, less than 85 μm, or less than 70 μm. In the manner described, there is no particular restriction on the lower limit of the surface roughness Sz of the above-mentioned smooth surface, for example, it can be more than 1 μm, more than 5 μm, more than 10 μm, more than 25 μm, or more than 40 μm. The surface roughness Sz of the above-mentioned smooth surface is less than 100 μm and not too small, which is advantageous from the perspective of improving the peel strength.
[0136] In addition, in this specification, a rough surface typically refers to a surface with a surface roughness Sz of 200 μm or more and 1000 μm or less. The adhesive sheet disclosed herein can preferably be used in a manner in which another adhesive surface is pressed against a surface (i.e., a rough surface) with a surface roughness Sz of 200 μm or more and 1000 μm or less. The surface roughness Sz of the rough surface is more preferably 250 μm or more, 450 μm or more, or 650 μm or more. In addition, the surface roughness Sz of the rough surface can be, for example, 850 μm or less, 700 μm or less, 500 μm or less, or 350 μm or less.
[0137] Here, in this specification, surface roughness Sz is the three-dimensional surface roughness defined in ISO25178, which refers to the maximum height in the measurement object area, that is, the distance in the height direction from the highest point to the lowest point. The surface roughness Sz can be measured using a 3D measurement laser microscope (for example, a product name "LEXT OLS4000" manufactured by Olympus Corporation). The specific measurement operation and measurement conditions can be appropriately set according to the measurement object and the measurement device. The surface roughness Sz recorded in the embodiments described below is measured using the product name "LEXT OLS4000" manufactured by Olympus Corporation under the conditions of objective lens: 20 times and measurement area: 660μm×660μm.
[0138] There is no particular limitation on the material constituting the above-mentioned smooth surface, and for example, it may be a resin material such as acrylonitrile-butadiene-styrene copolymer resin, polyolefin resin (polyethylene resin, polypropylene resin, ethylene-vinyl acetate copolymer, etc.), polystyrene resin, polycarbonate resin, acrylic resin, PET resin, etc.; inorganic materials such as glass and ceramics; metal materials such as stainless steel (SUS), aluminum, galvanized steel plate, etc.; rubber materials such as natural rubber and synthetic rubber; elastomeric materials such as olefin thermoplastic elastomers and styrene thermoplastic elastomers; composite raw materials thereof; etc. The above-mentioned smooth surface may be the surface of a member at least of which the surface is constituted by such a material. As a preferred example of the above-mentioned smooth surface, a molded body or a film comprising any of the above-mentioned resin materials may be cited. The above-mentioned smooth surface is typically a non-porous surface. The above-mentioned smooth surface may also be, for example, the surface of a plastic corrugated board, a non-porous surface in a member having pores such as the surface of a resin film in a laminate of a foam and a resin film, etc.
[0139] The rough surface is preferably the surface of a porous body. There is no particular limitation on the constituent material of the porous body, and it may be, for example, natural fibers, chemical fibers (synthetic fibers) as described above; inorganic fibers such as glass fibers and carbon fibers; metal fibers; and other fibrous substances. The rough surface may be a woven fabric, a non-woven fabric (a concept including paper and felt), a knitted fabric, a net, etc. obtained by spinning such fibrous substances alone or in a blend. The porous body may be a foam. Non-limiting examples of the foam mentioned here include: polyolefin resin foams such as polyethylene foam and polypropylene foam; polyester resin foams such as polyethylene terephthalate foam, polyethylene naphthalate foam, and polybutylene terephthalate foam; polyvinyl chloride resin foams such as polyvinyl chloride foam; vinyl acetate resin foam; polyphenylene sulfide resin foam; amide resin foams such as aliphatic polyamide (nylon) resin foam and wholly aromatic polyamide (aramid) resin foam; polyimide resin foam; polyether ether ketone (PEEK) foam; styrene resin foams such as polystyrene foam; urethane resin foams such as polyurethane resin foam; rubber resin foams such as chloroprene rubber foam; etc. Such a foamed body may be a continuous cell structure or an independent cell structure. Alternatively, the rough surface may be the surface of a non-porous body (e.g., a non-porous body composed of a resin material, an inorganic material, a metal material, an elastomeric material, or a composite material thereof), or the surface of a porous body laminated with a non-porous body. The rough surface may be the surface of a sheet-like member.
[0140] The adhesive sheet disclosed herein can be preferably used, for example, to fix the porous sheet to the core periphery of the brush roller of a vacuum cleaner. The core body is usually constructed to be roughly rod-shaped or cylindrical as a whole. The brush roller is sometimes also called a rotating brush or a head brush, and is typically installed at the suction port of the vacuum cleaner, and is constructed to rotate around the axis of the core body. At this time, the porous sheet (hereinafter also referred to as "brush cloth") fixed to the outer periphery of the core body rotates while contacting the cleaning object surface, and plays a role in guiding the removal object on the cleaning object surface into the vacuum cleaner. As the brush cloth, the fiber sheet (for example, a felt made of synthetic fibers such as polyamide), a foam sheet, a suede fabric, and a Velcro tape can be preferably used. There is no particular limitation on the thickness of the brush cloth, and for example, it can be about 0.01 mm to about 100 mm (preferably about 0.05 mm to about 10 mm). The back side of the brush cloth, that is, the surface that contacts the outer periphery of the core may be the rough surface (for example, a surface having a surface roughness Sz of 450 μm to 1000 μm). The outer periphery of the core may be the smooth surface.
[0141] In recent years, with the improvement of the performance of vacuum cleaners, the rotation speed of the brush roller tends to increase, so the adhesive sheet that fixes the brush cloth to the periphery of the core is required to have a higher adhesive ability. On the other hand, from the viewpoint of effective utilization of resources, the above-mentioned brush roller is preferably constructed in a manner that allows it to be peeled off (re-peeled off) from the frame and re-pasted in the correct position even if it is pasted in the wrong position during pasting. Considering that it is firmly adhered to both the smooth surface and the rough surface and has good re-peelability from the above-mentioned smooth surface, the adhesive sheet disclosed herein is suitable for the purpose of fixing the brush cloth to the periphery of the core of the brush roller. As the above-mentioned adhesive sheet, it is preferred to use a double-sided adhesive sheet, which has a first adhesive layer stacked on the first side of the fiber sheet and a second adhesive layer stacked on the second side of the fiber sheet. The above-mentioned brush cloth is fixed to the periphery of the above-mentioned core by bonding one of the first adhesive layer and the second adhesive layer (for example, the second adhesive layer) to the back of the brush cloth and bonding the other (for example, the first adhesive layer) to the periphery of the core.
[0142] As another preferred use of the adhesive sheet disclosed herein, the use of fixing the back side of the hook and loop fastener on the installation object can be exemplified. The above-mentioned adhesive sheet can also be satisfactorily used to fix any one of the male and female components of the hook and loop fastener. For example, it is suitable for fixing the hook and loop fastener with a back side composed of a non-woven fabric. The above-mentioned non-woven fabric can be, for example, a spunbond nonwoven web (i.e., a non-woven fabric obtained by a spunbond method, the same below), a meltblown nonwoven web, a spunlace nonwoven web, a spunbond meltblown spunbond nonwoven web, a non-bonded nonwoven web, an electrospun nonwoven web, a flash spun nonwoven web (for example, TYVEK of DuPont). TM), combed nonwoven fabrics, raised nonwoven fabrics (for example, nonwoven fabrics obtained by thermal bonding, adhesive bonding, spunlace, and hot air), etc. It can also be a laminate of nonwoven fabrics of different fibers (for example, a laminate of spunbond nonwoven web / meltblown nonwoven web / spunbond nonwoven web, etc.). There is no particular restriction on the fibers constituting the nonwoven fabric, for example, it can be selected from polyolefin fibers such as polypropylene fibers, polyethylene fibers, and α-olefin copolymer fibers; polyester fibers such as PET fibers, polylactic acid fibers, and polyglycolic acid fibers; and one or more of polyamide fibers, polyurethane fibers, elastomeric fibers, rayon fibers, cellulose fibers, and acrylic fibers. As preferred examples of fibers constituting the above-mentioned nonwoven fabric, polyolefin fibers (for example, polypropylene fibers) and polyester fibers (for example, PET fibers) can be listed. The back of the Velcro can be the above-mentioned rough surface (for example, a surface with a surface roughness Sz of 450 μm or more and 850 μm or less). The adhesive sheet disclosed herein can be firmly glued on any one of the smooth surface and the rough surface, so it can be satisfactorily used for fixing the back side of the hook and loop fastener on the smooth surface or the rough surface (preferably the smooth surface) of the installation object. As the above-mentioned adhesive sheet, it is preferred to use a double-sided adhesive sheet, which has a first adhesive layer stacked on the first side of the fiber sheet and a second adhesive layer stacked on the second side of the fiber sheet. By engaging one of the first adhesive layer and the second adhesive layer (such as the second adhesive layer) with the back side of the hook and loop fastener and engaging the other (such as the first adhesive layer) with the installation object, the above-mentioned hook and loop fastener is fixed on the above-mentioned installation object.
[0143] According to the present specification, there is provided an adhesive component, the adhesive component comprising: a double-sided adhesive sheet, the double-sided adhesive sheet having a first adhesive layer laminated on the first side of a fiber sheet and a second adhesive layer laminated on the second side of the fiber sheet; and a sheet-like component, the sheet-like component having a rough surface (for example, a rough surface with a surface roughness Sz of 200 μm to 1000 μm), the second adhesive layer of the adhesive sheet being bonded to the rough surface. The first adhesive layer and the second adhesive layer can each be any one of the adhesive layers disclosed herein. Figure 2 The cross-sectional structure of an adhesive member according to one embodiment is schematically shown in FIG. Figure 1Surface 12A of the second adhesive layer 12 of the double-sided adhesive sheet 1 of the same structure is bonded to one surface 50A (a rough surface with a surface roughness Sz of 200μm to 1000μm) of the sheet-like component 50. The thickness of the first adhesive layer 11 and the second adhesive layer 12 are both greater than 100μm and less than 190μm, for example, both are greater than 140μm and less than 180μm. The sheet-like component 50 is, for example, a female component of a Velcro tape, and surface 50A is its back side. The adhesive component 100 is a female component of a Velcro tape with an adhesive, and the surface 11A of the first adhesive surface 11 can be adhered to any installation object for use. In this way, the female component of the Velcro tape (sheet-like component 50) can be fixed to the above-mentioned installation object. As a modification of the adhesive component 100 of the above-mentioned method, the following can be listed: Figure 2 The sheet member 50 shown is, for example, in the form of a male member of a hook and loop fastener, in the form of a brush cloth of a brush roller of a vacuum cleaner, etc. The sheet member 50 may be, for example, a woven fabric, a nonwoven fabric (a concept including paper and felt), a knitted fabric, a net, a foam sheet, etc., made of the above-mentioned materials.
[0144] In the adhesive component disclosed herein, the 180-degree peel strength (hereinafter also referred to as "the ABS peel strength of the adhesive component") measured by sticking the first adhesive layer of the adhesive sheet constituting such an adhesive component on an ABS resin plate (typically a smooth surface with a surface roughness Sz of less than 100 μm) is preferably 25N / 20mm or more. Utilizing such an adhesive component, the sheet-like component can be firmly fixed to the adherend with good re-peelability. In some embodiments, the ABS peel strength of the adhesive component can be, for example, 10N / 20mm or more, and from the perspective of the reliability of adhesion to the adherend, it can be 15N / 20mm or more, 20N / 25mm or more, or 25N / 20mm or more. There is no particular restriction on the upper limit of the ABS peel strength of the adhesive component. In some ways, the above-mentioned peel strength to ABS is, for example, less than 100N / 20mm. From the viewpoint of suppressing the adhesive residue (paste residue) on the adherend surface after peeling, it is preferably less than 80N / 20mm, less than 70N / 20mm, or less than 65N / 20mm. The adhesive sheet disclosed herein is preferably peeled off at the interface between the adherend and the adhesive sheet in the determination of the above-mentioned 180-degree peel strength without causing the adhesive residue to remain on the ABS plate as the adherend. According to such an adhesive sheet, it is possible to appropriately take into account the high peel strength of the fixing and bonding of the components suitable for constituting various products and the good non-paste residue when separating the components and the adhesive sheet when the components are reused.
[0145] The matters disclosed according to this specification include the following.
[0146] (1) An adhesive sheet comprising a fiber sheet and an adhesive layer laminated on the fiber sheet, wherein:
[0147] The adhesive layer comprises a base polymer and a tackifying resin.
[0148] The base polymer is a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound.
[0149] The tackifying resin contains a tackifying resin having a softening point of less than 120°C and a tackifying resin having a softening point of more than 120°C, and
[0150] The adhesive layer has a thickness greater than 100 μm and less than 190 μm.
[0151] (2) The adhesive sheet according to (1) above, wherein the adhesive sheet is in the form of a double-sided adhesive sheet, the double-sided adhesive sheet having:
[0152] a first adhesive layer, the first adhesive layer being the adhesive layer laminated on the first surface of the fiber sheet; and
[0153] A second adhesive layer, wherein the second adhesive layer is the adhesive layer laminated on the second surface of the fiber sheet.
[0154] (3) The adhesive sheet according to (1) or (2) above, which is used to bond a smooth surface having a surface roughness Sz of less than 100 μm to a rough surface having a surface roughness Sz of 200 μm to 1000 μm.
[0155] (4) The pressure-sensitive adhesive sheet according to any one of (1) to (3) above, wherein the fiber sheet has a thickness of 15 μm to 50 μm, and a bulk density of 0.25 g / cm 3 Above and 0.50g / cm 3 the following.
[0156] (5) The pressure-sensitive adhesive sheet according to any one of (1) to (4) above, wherein the bulk density of the fiber sheet is greater than 0.35 g / cm 3 And less than or equal to 0.50g / cm 3 .
[0157] (6) The pressure-sensitive adhesive sheet according to any one of (1) to (5) above, wherein the thickness of the pressure-sensitive adhesive sheet is 4 times or more the thickness of the fiber sheet.
[0158] (7) The adhesive sheet according to any one of (1) to (6) above, wherein the adhesive sheet has a 180-degree peel strength to a stainless steel plate of 40 N / 20 mm or more.
[0159] (8) The adhesive sheet according to (7) above, wherein in the measurement of the 180-degree peel strength, peeling is performed at the interface between the stainless steel plate and the adhesive sheet.
[0160] (9) The pressure-sensitive adhesive sheet according to any one of (1) to (7) above, wherein the fibrous material constituting the fiber sheet is natural fiber.
[0161] (10) The pressure-sensitive adhesive sheet according to any one of (1) to (9) above, wherein the fiber sheet is a nonwoven fabric.
[0162] (11) The pressure-sensitive adhesive sheet according to any one of (1) to (10) above, wherein the total thickness of the pressure-sensitive adhesive sheet is greater than 150 μm.
[0163] (12) The pressure-sensitive adhesive sheet according to any one of (1) to (11) above, wherein the pressure-sensitive adhesive sheet is used to fix a porous sheet to the outer periphery of a core of a brush roller of a vacuum cleaner.
[0164] (13) The pressure-sensitive adhesive sheet according to any one of (1) to (11) above, wherein the pressure-sensitive adhesive sheet is used to fix the back surface of a hook and loop fastener to an object to be attached.
[0165] (14) A method for producing a pressure-sensitive adhesive sheet, which is the method for producing a pressure-sensitive adhesive sheet according to any one of (1) to (13) above, wherein the method for producing a pressure-sensitive adhesive sheet comprises:
[0166] preparing the above-mentioned fiber sheet;
[0167] forming the adhesive layer from an adhesive composition comprising the base polymer and the tackifying resin; and
[0168] The adhesive layer is laminated on the fiber sheet.
[0169] (15) A pressure-sensitive adhesive member comprising the pressure-sensitive adhesive sheet according to any one of (2) to (11) above and a sheet-like member having a rough surface with a surface roughness Sz of 200 μm to 1000 μm, wherein:
[0170] The second pressure-sensitive adhesive layer of the pressure-sensitive adhesive sheet is bonded to the rough surface.
[0171] (16) The adhesive member according to the above (15), wherein the rough surface of the sheet-like member is the back surface of the male member or the back surface of the female member of the hook and loop fastener.
[0172] (17) The adhesive member according to the above (16), wherein the rough surface of the sheet-like member is the back surface of a brush cloth fixed to the outer periphery of a core of a brush roller of a vacuum cleaner.
[0173] (18) The adhesive member according to any one of (15) to (17) above, wherein the 180-degree peel strength measured by affixing the first adhesive layer of the adhesive sheet to an ABS resin plate is 25 N / 20 mm or more.
[0174] (19) The adhesive member according to the above (18), wherein in the measurement of the 180-degree peel strength, peeling is performed at the interface between the ABS plate and the adhesive sheet.
[0175] [Example]
[0176] Hereinafter, some embodiments of the present invention will be described, but it is not intended to limit the present invention to the embodiments. It should be noted that in the following description, unless otherwise specified, "parts" and "%" are weight references. In addition, each characteristic in the following description was measured or evaluated in the following manner.
[0177] <Preparation of Adhesive Composition>
[0178] (Adhesive composition A)
[0179] An adhesive composition (adhesive composition A) of NV50% was prepared by stirring and mixing 100 parts of a styrene-isoprene block copolymer as a base polymer (manufactured by Nippon Zeon Corporation, product name "Quintac 3520", styrene content 15%, diblock ratio 78%), 20 parts of an aromatic petroleum resin (manufactured by JX Nippon Mining and Energy Corporation, product name "Nippon Oil Neopolymer 150", softening point 155°C, hydroxyl value less than 1 mgKOH / g), 40 parts of a terpene-phenol resin, 30 parts of a terpene resin, 0.75 parts of an isocyanate compound based on solid content (manufactured by Tosoh Corporation, product name "Coronate L"), 3 parts of an antioxidant and toluene as a solvent.
[0180] Here, as the terpene-phenol resin, the product name "YS Polystar S145" (softening point 145°C, hydroxyl value 100 mgKOH / g) manufactured by Yasuhara Chemical Co., Ltd. and the product name "YS Polystar T145" (softening point 145°C, hydroxyl value 60 mgKOH / g) manufactured by Yasuhara Chemical Co., Ltd. were used in a mass ratio of 1:1 so that their total amount was 40 parts. As the terpene resin, the product name "YS RESIN PX1150N" (softening point 115°C, hydroxyl value less than 1 mgKOH / g) manufactured by Yasuhara Chemical Co., Ltd. was used. As the antioxidant, the product name "IRGANOX CB612" manufactured by BASF was used (a blend of the product name "IRGAFOS 168" manufactured by BASF and the product name "IRGANOX 565" manufactured by BASF in a mass ratio of 2:1).
[0181] (Adhesive composition B)
[0182] In a reaction vessel equipped with a stirrer, a thermometer, a nitrogen inlet tube and a reflux condenser, 100 parts of n-butyl acrylate (BA) as monomer components, 5 parts of vinyl acetate (VAc), 3 parts of acrylic acid (AA) and 0.1 parts of 2-hydroxyethyl acrylate (HEA), 0.35 parts of 2,2'-azobisisobutyronitrile (AIBN) as a polymerization initiator, and toluene as a polymerization solvent were added, and solution polymerization was carried out in a nitrogen stream to obtain a solution of an acrylic polymer. To this solution, 2 parts (converted to solid content) of an isocyanate crosslinking agent (trade name "Coronate L", manufactured by Tosoh Corporation) were added to 100 parts of the acrylic polymer contained in the solution to prepare an adhesive composition (adhesive composition B).
[0183] <Preparation of adhesive sheets>
[0184] (Example 1)
[0185] A sheet-like release liner was prepared, which was obtained by laminating a polyethylene layer having a thickness of 25 μm on one side of wood-free paper and subjecting the same to a release treatment using a polysiloxane-based release agent. The adhesive composition A obtained above was applied to the release-treated side of the release liner and dried, thereby forming an adhesive layer having a thickness of 150 μm on the release liner. The adhesive layer was bonded to the first side of the fiber sheet S to prepare a first adhesive layer. As the fiber sheet A, a 49 μm thick fiber sheet with a bulk density of 0.469 g / cm 3 , basis weight is 23g / m 2Pulp nonwoven fabric. Similarly, an adhesive layer with a thickness of 150 μm was formed on the release liner, and it was attached to the second side of the fiber sheet S to prepare a second adhesive layer. In this way, a laminated body was obtained in which the first adhesive layer and the second adhesive layer were laminated on the first side and the second side of the fiber sheet respectively, and the surface of each adhesive layer was protected by the release liner. Then, the laminated body was passed through a laminator at 100°C once under the conditions of a pressure of 0.3 MPa and a speed of 0.5 m / min, and then aged at 23°C for 1 hour, thereby obtaining the double-sided adhesive sheet involved in this example.
[0186] (Comparative Examples 1 to 3)
[0187] Double-sided PSA sheets according to Comparative Examples 1 to 3 were prepared in the same manner as in Example 1 except that the thicknesses of the first PSA layer and the second PSA layer were changed as shown in Table 1.
[0188] (Comparative Example 4)
[0189] A double-sided PSA sheet according to Comparative Example 4 was prepared in the same manner as in Example 1 except that PSA composition B was used instead of PSA composition A.
[0190] <Measurement of 180-degree peel strength>
[0191] (Peel strength to rough surface)
[0192] The release liner covering the first adhesive surface of the adhesive sheet involved in each example was peeled off, and a polyethylene terephthalate (PET) film with a thickness of 25 μm was pasted and backed. The backed adhesive sheet was cut into a size of 20 mm in width and 100 mm in length to prepare a test piece. Under an environment of 23°C and 50% RH, the release liner covering the second adhesive surface of the test piece was peeled off, and the test piece was pressed onto the surface of the felt as an adherend (maximum height Sz=761 μm) using a roll laminator under the conditions of 100°C, 0.3MPa, and 0.3m / min. As an adherend, the trade name "Himelon SP30B" (pressed felt with wool as the main raw material) manufactured by Anbi Ke Co., Ltd. was used. It was placed under the same environment for 30 minutes, and then according to JIS Z 0237, the 180° peeling adhesion (N / 20mm) was measured using a tensile tester at a tensile speed of 300mm / min. The measurement was performed three times (ie, N=3), and the arithmetic mean value thereof was calculated.
[0193] (Peel strength to smooth surface)
[0194] The adhesive sheets involved in each example were cut into a size of 20 mm in width and 100 mm in length to prepare test pieces. The release liner covering the second adhesive surface of the test piece was peeled off, and the test piece was crimped onto the surface of the trade name "Himelon SP30B" manufactured by Ambico Co., Ltd. using a roll laminator at 100°C, 0.3 MPa, and 0.3 m / min. Next, the release liner covering the first adhesive surface of the test piece was peeled off, and the test piece was crimped onto the surface of the adherend (maximum height Sz = 58 μm) by using a 2 kg roller to and fro once. As the adherend, an acrylonitrile-butadiene-styrene copolymer resin plate (ABS plate) manufactured by Shin Kobe Electric Co., Ltd. was used. It was placed under the same environment for 30 minutes, and then the 180° peeling adhesion (N / 20 mm) was measured using a tensile tester at a tensile speed of 300 mm / min according to JIS Z 0237. The measurement was performed three times (ie, N=3), and the arithmetic mean value thereof was calculated.
[0195] In the measurement of the peel strength on the smooth surface, the final product obtained by pressing the second adhesive surface of the test piece onto the felt can be regarded as an adhesive member obtained by bonding the second adhesive layer of the test piece onto the felt as a sheet-like member.
[0196] Table 1
[0197]
[0198] As shown in Table 1, the thickness of the adhesive layer is greater than 100 μm and less than 190 μm. The adhesive sheet of Example 1 shows high peel strength on both the rough surface and the smooth surface. In addition, the peel strength ratio (rough surface / smooth surface) of the adhesive sheet of Example 1 is greater than 1. It should be noted that when the peel strength of the adhesive sheet of Example 1 on the smooth surface was measured, no adhesive residue was found on the ABS plate.
[0199] <Production of adhesive member>
[0200] (Example 2)
[0201] The adhesive sheet of Example 1 was cut into a size of 20 mm in width and 100 mm in length to prepare a test piece. The release liner covering the first adhesive surface of the test piece was peeled off and pressed onto the back side (maximum height Sz = 761 μm) of the female member of a hook and loop fastener (manufactured by Trusco Nakayama, trade name "Free Velcro Single-sided MKT-25B") as a sheet-like member using a roll laminator at 100°C, 0.3 MPa, and 0.3 m / min to obtain the adhesive member involved in this example.
[0202] (Example 3)
[0203] The adhesive member according to this example was obtained in the same manner as in Example 2 except that a nonwoven fabric (pulp nonwoven fabric manufactured by Daifuku Paper Industries, Ltd., trade name “SP-14K”, maximum height) was used as the sheet-like member.
[0204] <Measurement of 180-degree peel strength>
[0205] (Peel strength to rough surface)
[0206] For the adhesive sheet of Example 1, the 180-degree peel strength against the sheet-like member used in Examples 2 and 3 was measured. That is, the release liner covering the first adhesive surface of the adhesive sheet of Example 1 was peeled off, and a PET film with a thickness of 25 μm was attached to provide a backing. The backed adhesive sheet was cut into a size of 20 mm in width and 100 mm in length to prepare a test piece. Under an environment of 23°C and 50% RH, the release liner covering the second adhesive surface of the test piece was peeled off, and the test piece was pressed onto the surface of the sheet-like member (adherend) used in Examples 2 and 3 using a roll laminator under the conditions of 100°C, 0.3 MPa, and 0.3 m / min. It was placed under the same environment for 30 minutes, and then the 180° peel adhesive force (N / 20 mm) was measured using a tensile tester at a tensile speed of 300 mm / min according to JIS Z 0237. The measurement was performed 3 times (i.e., N=3), and their arithmetic mean was calculated.
[0207] (Peel strength to smooth surface)
[0208] The adhesive sheets involved in each example were cut into a size of 20 mm in width and 100 mm in length to prepare test pieces. The release liner covering the second adhesive surface of the test piece was peeled off, and the test piece was crimped onto the surface of the sheet-like member (adherend) used in Examples 2 and 3 using a roll laminator at 100°C, 0.3 MPa, and 0.3 m / min. Next, the release liner covering the first adhesive surface of the test piece was peeled off, and the test piece was crimped onto the surface of the above-mentioned ABS board as the adherend using a 2 kg roller back and forth once. It was placed under the same environment for 30 minutes, and then the 180° peeling adhesion (N / 20mm) was measured using a tensile tester at a tensile speed of 300 mm / min according to JIS Z0237. The measurement was performed 3 times (i.e., N=3), and their arithmetic mean was calculated.
[0209] The obtained results are shown in Table 2 together with the evaluation results of the pressure-sensitive adhesive sheet of Example 1.
[0210] Table 2
[0211]
[0212] As shown in the column of the rough surface peel strength of Examples 2 and 3 in Table 2, the adhesive sheet of Example 1 also showed a high peel strength equal to or higher than that of the felt for the back side of the hook and loop fastener and the nonwoven fabric as the sheet-like member with the rough surface. In addition, the adhesive member in which the second adhesive surface of the adhesive sheet of Example 1 was bonded to the rough surface of each sheet-like member showed a high peel strength for the ABS board, and when the peel strength was measured, no adhesive was found to remain on the ABS board.
[0213] Although specific examples of the present invention have been described in detail above, these specific examples are merely illustrative and do not limit the claims. The technology described in the claims includes various modifications and changes to the specific examples described above.
[0214] Reference numerals
[0215] 1 Double-sided adhesive sheet (adhesive sheet)
[0216] 11. First adhesive layer
[0217] 11A First bonding surface
[0218] 12 Second adhesive layer
[0219] 12A Second bonding surface
[0220] 15 Fiber Sheet
[0221] 21 Release liner
[0222] 21B Back
[0223] 50 Sheet Components
[0224] 50A Surface (rough surface)
[0225] 100 Adhesive member
Claims
1. An adhesive sheet comprising a fiber sheet and an adhesive layer laminated on the fiber sheet, wherein: The bulk density of the fiber sheet is greater than 0.35 g / cm 3 And less than or equal to 0.50g / cm 3 The thickness of the fiber sheet is greater than or equal to 15 μm and less than or equal to 50 μm, and the basis weight of the fiber sheet is 15 g / m 2 Above and 25g / m 2 the following, The adhesive layer comprises a base polymer and a tackifying resin, The base polymer is a block copolymer of a monovinyl-substituted aromatic compound and a conjugated diene compound. The tackifying resin contains a tackifying resin having a softening point of less than 120°C and a tackifying resin having a softening point of more than 120°C, and The thickness of the adhesive layer is greater than 100 μm and less than 190 μm, The ratio of the peel strength of the adhesive sheet to the rough surface to the peel strength of the adhesive sheet to the smooth surface is greater than 1.0, wherein the peel strength of the adhesive sheet to the rough surface is measured by sticking the adhesive sheet to a rough surface having a surface roughness Sz of 200 μm to 1000 μm, and the peel strength of the adhesive sheet to the smooth surface is measured by sticking the adhesive sheet to an acrylonitrile-butadiene-styrene copolymer resin plate having a surface roughness Sz of less than 100 μm.
2. The adhesive sheet according to claim 1, wherein The adhesive sheet is in the form of a double-sided adhesive sheet, and the double-sided adhesive sheet has: a first adhesive layer, the first adhesive layer being the adhesive layer laminated on the first side of the fiber sheet; and A second adhesive layer, the second adhesive layer is the adhesive layer laminated on the second surface of the fiber sheet.
3. The adhesive sheet according to claim 1, wherein The adhesive sheet is used to bond a smooth surface having a surface roughness Sz of less than 100 μm to a rough surface having a surface roughness Sz of 200 μm to 1000 μm.
4. The adhesive sheet according to claim 1, wherein The thickness of the adhesive sheet is at least 4 times the thickness of the fiber sheet.
5. The adhesive sheet according to claim 1, wherein The fibrous material constituting the fiber sheet is natural fiber.
6. The adhesive sheet according to claim 1, wherein The fiber sheet is non-woven fabric.
7. The adhesive sheet according to claim 1, wherein The total thickness of the adhesive sheet is greater than 150 μm.
8. The adhesive sheet according to claim 1, wherein The adhesive sheet is used to fix the porous sheet on the periphery of the core body of the brush roller of the vacuum cleaner.
9. The adhesive sheet according to claim 1, wherein The adhesive sheet is used to fix the back side of the hook and loop fastener to the object to be installed.
10. The adhesive sheet according to claim 2, wherein The adhesive sheet is used to bond a smooth surface having a surface roughness Sz of less than 100 μm to a rough surface having a surface roughness Sz of 200 μm to 1000 μm.
11. The adhesive sheet according to claim 2, wherein The thickness of the adhesive sheet is at least 4 times the thickness of the fiber sheet.
12. The adhesive sheet according to claim 2, wherein The fibrous material constituting the fiber sheet is natural fiber.
13. The adhesive sheet according to claim 2, wherein The fiber sheet is non-woven fabric.
14. The adhesive sheet according to claim 2, wherein The total thickness of the adhesive sheet is greater than 150 μm.
15. The adhesive sheet according to claim 2, wherein The adhesive sheet is used to fix the porous sheet on the periphery of the core body of the brush roller of the vacuum cleaner.
16. The adhesive sheet according to claim 2, wherein The adhesive sheet is used to fix the back side of the hook and loop fastener to the object to be installed.
17. A method for producing a pressure-sensitive adhesive sheet, which is the method for producing a pressure-sensitive adhesive sheet according to any one of claims 1 and 3 to 9, wherein: The method for manufacturing the adhesive sheet comprises: preparing the fiber sheet; forming the adhesive layer from an adhesive composition comprising the base polymer and the tackifying resin; and The adhesive layer is laminated on the fiber sheet.
18. A method for producing a pressure-sensitive adhesive sheet, which is the method for producing a pressure-sensitive adhesive sheet according to any one of claims 2 and 10 to 16, wherein: The method for manufacturing the adhesive sheet comprises: preparing the fiber sheet; forming the first adhesive layer and the second adhesive layer from an adhesive composition comprising the base polymer and the tackifying resin; and The first adhesive layer and the second adhesive layer are laminated on the fiber sheet.
19. An adhesive member comprising the adhesive sheet according to any one of claims 2 and 10 to 16 or the adhesive sheet produced by the method for producing an adhesive sheet according to claim 18 and a sheet-like member having a rough surface with a surface roughness Sz of 200 μm to 1000 μm, wherein: The second adhesive layer of the adhesive sheet is bonded to the rough surface.
20. The adhesive member according to claim 19, wherein The rough surface of the sheet-like component is the back surface of the male component or the back surface of the female component of the hook and loop fastener.
21. The adhesive member of claim 19, wherein The rough surface of the sheet-like member is the back side of the brush cloth fixed to the periphery of the core body of the brush roller of the vacuum cleaner.